Pendidikan Kesehatan Tentang Masalah Status Gizi Ibu Hamil - Riezqy Ariendha, Dian Soekmawaty; Setyawati, Irni; Utami, Kusniyati; Fatmawati , Nurul; Hardaniyati, Hardaniyati (Lembaga Dongan Dosen, 2025)
Pregnancy is a period that greatly determines the quality of human resources in the future because the growth and development of a child is determined since the fetus is in the womb. Pregnant women are one of the groups that are vulnerable to nutritional problems such as Chronic Energy Deficiency (CED). One way to improve the nutritional status of pregnant women is to provide education about the nutritional status of pregnant women. The purpose of this community service activity is to improve mothers' understanding of nutritional problems in pregnant women as an effort to prevent CED in pregnant women. The method used in this community service stage consists of 3 stages, namely pretest, then Health Education about the nutritional status of pregnant women to prevent CED, then continued with the post-test process to determine the level of knowledge of pregnant women. Results: The results of the post-test showed an increase in knowledge, with 23 (76.6%) pregnant women having good knowledge and 23.3% of pregnant women having sufficient knowledge about the nutrition of pregnant women. Conclusion: The community service activities carried out are expected to make mothers better understand the nutritional status of pregnant women and how to prevent it in pregnant women. The material provided is in the form of knowledge about the nutritional status of pregnant women and is delivered in a straightforward and clear manner. The community is enthusiastic about participating in community service activities considering the great benefits that can be obtained from community service activities.